Pengetahuan Pengasuhan, Maternal Self-Efficacy, Praktik Pengasuhan, Riwayat Kelahiran, dan Perkembangan Motorik Anak Baduta - Iftitahun Nabilah; Dwi Hastuti; Melly Lathifah (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2022)
The influence of birth history and mother's parenting to motor development have been widely studied. However the importance of parenting knowledge and maternal self-efficacy is not yet clear. This study aims to analyze the effect of parenting knowledge, maternal self-efficacy, parenting practices and birth history to motor development of children aged 1-2 years old. This research is explanatory. The research location was chosen purposively in 5 selected villages is Panggang city, Karangturi city, Wonorejo city, Glagah city, Konang city, in Glagah sub-district in Lamongan city . The population of this study was family has children aged 12-24 months, and from 5 selected villages, 104 children were obtained. The data collected using the self-report method and analyzed using Structural Equation Modelling (SEM). Results of this study showed that parenting practice (β=4.308; t>1.96) had a positive effect to motor development of children. Parenting practice influenced by maternal self-efficacy (β=3.861; t>1.96), and maternal self-efficacy influenced by parenting knowledge (β=3.472; t>1.96). Parenting knowledge had a specific indirect effect to motor development through maternal self-efficacy and parenting practice (β=2.043;t>1.96).. Parenting knowledge had a specific indirect effect to parenting practice through maternal self-efficacy (β= 2.319; t>1.96). Maternal self-efficacy had a specific indirect effect to motor development through parenting practice (β= 2.685; t>1.96).